Vulnerability of the gay population living with HIV: an integrative review (Research, Society and Development, 2020)
The current study had the aim of identify the main vulnerabilities of the GAY population living with HIV (Human Immunodeficiency Virus). It was realized an integrative proofreading of scientific articles indexed in the first semestre of 2020, on the databases of Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) and on the electronic library of Scientific Electronic Library On-line (SciELO), applying the descriptors: HIV AND GAY AND VULNERABILITY. The scientific Productions included approach the different vulnerabilities faced by the gay population, in the three categories: individual, social and programmatic. The United Nations‘ (UN) data point out a prevalence of 21% in the cases of infection by HIV in Brazil between the years of 2008 and 2018. Such resurgence is observed in the GAY and MSM population (Men who have sex with men), which in 2007 represented 32% for 54% in 2017, with the majority of infected in the population of 15 until 29 years old, 1% em 2009 for 18,4% in 2019. The factors that corroborate for the increase of vulnerability are precocius sexual life, low adherence of condom, the difficulty to access health centers, discrimination, stigma and prejudice. It is important to emphasize that the insufficient availability of government resources retards the efforts to provide essential sevices and specific updates on the public policies to this population, contributing even more to the prevalence of vunerability. It is concluded that the study enabled synthesize the findings related to the main vunerabilities faced by the population, on the three categories and the nursing in conjuction with public authorities, have significant influence on the decrease of the vulnerabilities.